البنية الشخصية في رواية "أم سعد" لغسان كنفاني (Jurnal Adabiya, 2023)
The study discusses the forms of personal character structure in the novel "Umm Saad" by Ghassan Kanafani, due to the behavior of colors and the specifications of their internal elements. The approach in it is a descriptive and analytical approach, namely describing the novel and analyzing it with the inclusion of Sigmund Freud's literary psychology. The results obtained by the author are id quotes one, ego quotes four, and superego quotes one and that is the actual psychological reality, because the id is the inner world or human subjectivity, and there is no direct contact with the objective world. And the inner aspect contains things that are born from birth. Ego is the aspect of personality that is responsible for dealing with reality. As for id, it is a single quote because it is the inner world or human subjectivity, and has no direct relationship with the purpose of the world. The inner aspect contains biological elements of instinct and is also a "warehouse" of psychic energy that drives the ego and superego. And the ego is an empathetic quote to see that Umm Saad's ego position can overcome the nature of her identity. Superego quote one is actually very worried and wants to bring the kids home but he realizes that the kids are fighting for their country
Keywords: Character; novel; psychology